Cloud native storage behind the biggest 1-day shopping event in the world (O'Reilly Media, 2019)
"It's two minutes and five seconds after midnight on November 11, 2018; that's how long it took for the Alibaba platform to record RMB 10B worth of sales. At the 26 minute and 2 second mark, more than RMB 50B of goods were sold, and by the end of the day, a total of RMB 213.5B of goods were sold--the equivalent of $30.5 billion. Over half a billion people across 200 countries participated in this event with goods purchased from 180 thousand brands. Clearly, not only did a massive number of transactions take place in a short period of time, but a massive number of users were also concurrently browsing product information. At one point, the system reached 1.72B messages per second. And later that day, over 1B packages were shipped out to the buyers. Alex Chen (Alibaba Cloud) examines how a combination of cloud native storage products such as table storage, object storage, and log storage combined with serverless technologies were the backbone supporting such a massive workload."--Resource description page